State Authority and Religious Contestation: Resistance to Governmental Decisions on Islamic Calendar Determination in Indonesia - Ahmad Adib Rofiuddin; Mahsun Mahsun; Arifana Nur Kholiq (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2025)
The dynamics surrounding the determination of the beginning of the Hijri calendar remain a persistent and relevant issue within the Indonesian Muslim community. One notable example is the public resistance that emerged in response to the government’s decision regarding 1 Shawwal, which was perceived to neglect input from various stakeholders. This study aims to explore the forms of resistance and identify the underlying factors contributing to this phenomenon. Using a qualitative descriptive approach, data were collected from online news sources and other relevant materials, then categorized and analyzed. The findings reveal that resistance occurs not only at the organizational and group levels but also at the individual level. Furthermore, the study highlights that an individual's level of literacy and mastery of scientific knowledge significantly influences their understanding and acceptance of the calendar decision. By applying Social Representation Theory, this study offers a novel contribution to the literature by shifting the focus from legal-astronomical debates to the sociocultural meanings and identities that shape public responses. This perspective fills a gap in previous studies and provides a more holistic understanding of calendar-related conflicts. The study recommends a more extensive public education effort by the government, including the integration of related knowledge into formal school curricula, as a strategic investment for fostering greater social harmony in the future.